Natural Antibodies Produced in Vaccinated Patients and COVID-19 Convalescents Hydrolyze Recombinant RBD and Nucleocapsid (N) Proteins - Timofeeva, Anna M.; Shayakhmetova, Liliya Sh; Nikitin, Artem O.; Sedykh, Tatyana A.; Matveev, Andrey L.; Shanshin, Daniil V.; Volosnikova, Ekaterina A.; Merkuleva, Iuliia A.; Shcherbakov, Dmitriy N.; Tikunova, Nina V.; Sedykh, Sergey E.; Nevinsky, Georgy A. (Biomedicines, 2024)
Antibodies are protein molecules whose primary function is to recognize antigens. However, recent studies have demonstrated their ability to hydrolyze specific substrates, such as proteins, oligopeptides, and nucleic acids. In 2023, two separate teams of researchers demonstrated the proteolytic activity of natural plasma antibodies from COVID-19 convalescents. These antibodies were found to hydrolyze the S-protein and corresponding oligopeptides. Our study shows that for antibodies with affinity to recombinant structural proteins of the SARS-CoV-2: S-protein, its fragment RBD and N-protein can only hydrolyze the corresponding protein substrates and are not cross-reactive. By using strict criteria, we have confirmed that this proteolytic activity is an intrinsic property of antibodies and is not caused by impurities co-eluting with them. This discovery suggests that natural proteolytic antibodies that hydrolyze proteins of the SARS-CoV-2 virus may have a positive impact on disease pathogenesis. It is also possible for these antibodies to work in combination with other antibodies that bind specific epitopes to enhance the process of virus neutralization.